Characteristics and outcomes of in-hospital patients with Covid-19 and history of tuberculosis: a matched case-control from the Brazilian Covid-19 Registry - Rafael Lima Rodrigues de Carvalho; Daniella Nunes Pereira; Victor Schulthais Chagas; Valéria Maria Augusto; Felício Roberto Costa; Guilherme Fagundes Nascimento; Karen Brasil Ruschel; Leila Beltrami Moreira; Marcelo Carneiro; Milton Henriques Guimarães Júnior; Mônica Aparecida Costa; Naiara Patrícia Fagundes Bonardi; et al. (BMC Infectious Diseases)
Abstract Background The Covid-19 pandemic caused a negative impact on other infectious diseases control, prevention, and treatment. Consequently, low and middle-income countries suffer from other endemic diseases, such as tuberculosis. This study was designed to compare Covid-19 manifestations and outcomes between patients with previously treated tuberculosis and controls without this condition. Methods We performed a matched case-control study drawn from the Brazilian Covid-19 Registry data, including in-hospital patients aged 18 and over with laboratory-confirmed Covid-19 from March 1, 2020, to March 31, 2022. Cases were patients with a past history of tuberculosis. Controls were Covid-19 patients without a tuberculosis history. Patients were matched by hospital, sex, presence of HIV, and number of comorbidities, with a 1:4 ratio. Results Of 13,636 patients with laboratory-confirmed diagnoses of Covid-19 enrolled in this study, 80 had a history of tuberculosis. Statistical differences in history of chronic pulmonary obstructive disease (15% vs. 3.2%), psychiatric disease (10% vs. 3.5%,), chronic kidney disease (11.2% vs. 2.8%), and solid-organ transplantation; (5% vs. 0.9%, p < 0.05 for all) were higher in patients with a past history of tuberculosis. Prior use of inhalatory medications (5% vs. 0.6%,), oral corticoids (8.8% vs. 1.9%), immunosuppressants (8.8% vs. 1.9%,) and the use of illicit drugs were more common in the case group (6.2% vs. 0.3% p < 0.05for all). There were no significant differences in in-hospital mortality, mechanical ventilation, need for dialysis, and ICU admission. Conclusions Patients with a history of tuberculosis infection presented a higher frequency of use of illicit drugs, chronic pulmonary obstructive disease, psychiatric disease, chronic kidney disease, solid-organ transplantation, prior use of inhalatory medications, oral corticoids, and immunosuppressants. The outcomes were similar between cases and controls.